Eurocode7 on Geotechnical design: a code for soil‐structure interaction - Frank, Roger (Journal of Applied Engineering Science & Technology; Vol 1 No 1 (2014), 2014)
Eurocode 7 on 'Geotechnical design' is actively being implemented throughout Europe. Part 1 devoted to the 'General rules' was published by CEN in 2004. The National annexes and documents have been prepared for final implementation in the various European countries. After describing shortly the history of the development of Eurocode 7, this paper gives the main contents of the code, as well as some aspects of particular interest to the soil-structure interaction modelling: the design approaches (DA1, DA2 and DA3) for ULS verifications in persistent and transient design situations, SLS verifications and allowable movements of foundations. Résumé : L'Eurocode7  sur le "Calcul géotechnique" est maintenant activement mis en oeuvre à travers toute l'Europe. La Partie 1 sur les "Règles générales" a été publiée en 2004. Les Annexes Nationales et documents ont été préparés pour la promulgation finale dans les divers pays européens. Après une brève note historique sur le développement de l'Eurocode 7, la présente communication donne le contenu général du document, ainsi que certains aspects intéressants pour la modélisation de l’interaction sol-structure : les approches de calcul pour la vérification des états limites ultimes (ELU) en situations de calcul durables et transitoires, les vérifications des états limites de service (ELS) et les déplacements admissibles des fondations. Mots clés : Eurocode 7, calcul géotechnique, fondations, ouvrages de soutènement, interaction sol-structure, états limites.
Keywords: Eurocode 7, geotechnical design, foundations, retaining structures, soil-structure interaction, limit states